A Case of Hyper IgD and Periodic Fever Syndrome in Japan - Kawashima, Hisashi (Libertas Academica, 2008)
We report a four-year-old Japanese girl with hyper IgD and periodic fever syndrome. There is a first report of hyper IgD syndrome (HIDS) of which the genomic study was done in Japan. In this report a girl complained of periodic fever and abdominal symptoms accompanied with high levels of mevalonic acid in urine and serum. She has been well controlled by non-steroidal anti-inflammatory drugs (NSAIDs) for 3 years.